Certain solitons on α-cosymplectic manifolds - Sardar, A.; Sarkar, A. (Carpathian Mathematical Publications, 2024)
In the present paper, we characterize some solitons such as η-Einstein soliton, η-Yamabe soliton and Ricci-Yamabe soliton on α-cosymplectic manifolds. Furthermore, we characterize 3-dimensional α-cosymplectic manifolds with gradient Ricci-Yamabe soliton. Finally, we construct an example.